A systematic review and evaluation of procedures for the induction of speech among persons with developmental disabilities. (19th May 2017) - Mulhern, Teresa; Lydon, Sinéad; Healy, Olive; Mollaghan, Gerard; Ramey, Devon; Leoni, Mauro
ABSTRACT: Objective : Deficits in vocal speech are common among those with developmental disabilities. This review examines interventions for teaching speech to individuals who presented as nonspeaking, or with low levels of vocalizations at baseline, and assesses evidence-based practice in this area. Methods : Systematic searches identified 78 studies suitable for inclusion. These studies were evaluated in terms of (a) participants, (b) intervention, (c) intervention setting, (d) intervention agent, (e) treatment efficacy, (f) generalization and maintenance of treatment effects, and (g) research rigor. Results : A variety of interventions, primarily behavioral, intended to induce vocal speech were delivered to participants with developmental disabilities aged between six months and 57 years. Treatment efficacy was variable (PND M = 52.9%; range 0%–100%); however, results indicated that behavioral interventions constituted evidence-based practice. Non-behavioral strategies were shown to have received insufficient research evaluation to date. Conclusion : Results indicate that a number of procedures can induce speech among individuals with developmental disabilities.